Valuable metals in coals of the Russian Arctic zone - V.I. Vyalov; A.Kh. Bogomolov; A.V. Nastavkin; E.V. Kuzevanova; E.P. Shishov; A.A. Chernyshev (Georesursy, 2019)
The research results of rare and valuable metals and estimations of resources of these metals in the coal deposits of the Russian Arctic zone are presented. In coal deposits in the Arctic zone of Russia (Pechora, Lensky, Tungusky, Taimyrsky, Zyryansky coal basins, coal deposits of Chukotka, Kamchatka, Franz Josef Land) anomalous concentrations of trace elements (Sc, Ti, V, Ga, Ge, Sr, Y, Zr, Nb. Mo, Pd, REE, etc.) have been established. The metal contents in the coals of the Lensky and Zyryansky basins, the deposits of Kamchatka, and the Franz Josef Land are given. The results of electron microscopic studies of mineral inclusions (with local microanalysis for their diagnosis) of coals of the Russian Arctic are presented. The results of calculating the prognostic resources of TiO2, V2O5, Th, Y2O3, REE 2O3, Sc, Mo, Ga, and other metals in the studied deposits are given. It is shown that coal deposits of the Russian Arctic zone should be considered as an unconventional and promising source of valuable metals. It is necessary to conduct extensive studies of the metal content of coal basins and deposits in the Arctic zone of Russia and assess the geological resources of the valuable metals contained in them.